Killer Joe - Letts, Tracy 1965- (Theatre Communications Group, 2014)
""One of our most valuable playwrights."-Time Out New York"A hideously funny tabloid noir. Letts' balance of irony and empathy continues to impress."-LA WeeklyA definitively dysfunctional family gives in to its basest instincts and is forced to face hidden truths in this twisted modern-day fairy tale by the Pulitzer Prize-winning author of August: Osage County. Performed in fifteen countries and twelve languages since its 1998 stage debut, Killer Joe is "a terrifically tasty potboiler. It has the enjoyable hairpin turns of the standard mystery thriller, but it's the skewed shifting relationships that keep you hooked" (The New York Times). Now a critically acclaimed film adapted by the playwright and starring Matthew McConaughey.Tracy Letts is the author of the Pulitzer Prize- and Tony Award-winning play August: Osage County (soon to be a feature film starring Meryl Streep and Julia Roberts). His other plays include Bug, Superior Donuts, and Man from Nebraska, a finalist for the Pulitzer Prize. He is an ensemble member of the Steppenwolf Theatre Company in Chicago as playwright and actor. "
Keywords: Theaterstück